Efficiency as Mediator between Artifacts, Values and Cultural Organization Assumptions Employees Working On Effectiveness of Parliament Secretariat (Dprd) Riau Islands Provincial, Indonesia - Wibisono, Chablullah; Mujizat, Indrayanib, (International Journal of Engineering and Technology, 2018)
The secretariat parliament (DPRD) Riau Islands chosen as the object of research for allegedly there are gaps between the theory with facts empirically; namely conflict with a culture of bureaucracy, political culture a variable that is submitted for held research is: artifact culture, the assumption of culture, cultural values increasing efficiency, and effectiveness of work. Respondents the employees of the secretariat DPRD Riau Islands. The data processed with program statistics AMOS for windows version 22.0 to test normality, CFA and test leverage with SEM based on assumptions in structural equation unified ( SEM ) model, in this research the number of respondents who obtained a total of 109 respondents, then the amount of the sampled using the census as much as 109 respondents, to test the feasibility this research result can be summarized as follows, Effect of Cultural Artifacts to Efficiency are a significant positive, Effect of Cultural Values on Efficiency is positive, not substantial, Effect of Assumption on Efficiency is a significant positive, Effect of Cultural Artifacts to Effectiveness are a significant positive, Effect of Cultural Values on Effectiveness are a significant positive, Effect of Assumption Cultural to Effectiveness is positively not substantial,Â Â  Effect of Efficiency to Effectiveness significant positive, Efficiency changes are affected by Artifacts, Cultural Values and Cultural Assumptions 84.9%, while the effectiveness changes are affected by artifacts, Cultural Values, Assumptions Culture and Efficiency of 99.4%, Evidently there is a problem in the Riau Islands DPRD Secretariat, the gap between theory and empris answered, why there is performance hindrance of DPRD, one reason is the existence of two cultural organizations (bureaucratic and political) that interact in an institution DPRD Secretariat, to take a decision, is something unique in the organizational culture, so that positive outcomes are not significant.